Proactive personality and critical thinking in Chinese medical students: The moderating effects of psychological safety and academic self-efficacy - Wang, Yan-ping; Zhao, Chen-xi; Zhang, Shu-e; Li, Qing-lin; Tian, Jing; Yang, Mao-ling; Guo, Hai-chen; Yuan, Jia; Zhou, Sheng-yan; Wang, Min; Cao, De-pin (Frontiers in Psychology, 2022)
Objectives: This study aimed to identify the relationship among proactive personality, psychological safety, academic self-efficacy and critical thinking, and to further explore whether psychological safety and academic self-efficacy could be a moderator in the association between proactive personality and critical thinking among Chinese medical students. Materials and Methods: The cross-sectional study was carried out from October to December 2020 in China. Totally, 5920 valid responses were collected at four Chinese medical universities. Critical thinking, proactive personality, psychological safety, academic self-efficacy and demographic factors were assessed through questionnaires. Hierarchical multiple regression was used to identify interrelationship clusters among variables. Simple slope analyses were performed to explore the moderating effects of psychological safety and academic self-efficacy. Results: The mean score of critical thinking among medical students was 3.85 ± 0.61. Proactive personality, psychological safety, and academic self-efficacy were shown to be important factors for critical thinking. Psychological safety and academic self-efficacy moderated the association between proactive personality and critical thinking. A simple slope analysis showed that high psychological safety and academic self-efficacy weakened the impact of proactive personality on critical thinking. Conclusion: Most medical students surveyed in China might have relatively high levels of critical thinking. Psychological safety and academic self-efficacy moderated the association between proactive personality and critical thinking. More interventions related to psychological safety and academic self-efficacy will be helpful to improve critical thinking among Chinese medical students.